Non‐native palms (Arecaceae) as generators of novel ecosystems: A global assessment. Issue 11 (25th August 2020) - Fehr, Vincent; Buitenwerf, Robert; Svenning, Jens‐Christian
Abstract: Aims: Novel ecosystems are self‐maintaining ecosystems that support species assemblages without historical precedent. Despite much interest and controversy around novel ecosystems, it remains poorly understood how they are generated, what their capacity to support biodiversity is and what the implications for society are. Here, we address these issues through a global synthesis of non‐native palms, since palms are likely generators of novel ecosystems because they are introduced widely beyond their native range and have the capacity to act as ecosystem engineers. Location: Global. Methods: We gathered data on non‐native palms from peer‐reviewed literature/papers, grey literature and online databases. We extracted data on the biogeographic context of palm invasions, plant functional traits and anthropogenic drivers to quantify their effects on biodiversity, ecosystem functioning and ecosystem services. Results: Of the 2, 557 palm species, 3.4% (86 species) were recorded as naturalized and 1.1% (28 species) as invasive, which exceeds the average invasion success across all woody plants. Naturalized palms are present in most tropical and subtropical regions around the world, often in urban areas, reflecting the use of palms in horticulture. Many naturalized palms were taller and more likely to originate from open habitats or dry forest than non‐naturalized palms. These features likely represent the naturalized palms' competitive ability, high fecundity and dispersal ability along with ecological matching to human‐disturbed environments. Overall, literature on ecological effects of palm invasions was sparse, but we found multiple cases in which palm invasions resulted in strong ecosystem changes or even biome shifts. Main Conclusions: We found strong evidence that palm invasions can generate novel ecosystems. Although there are substantial knowledge gaps on the ecological effects of palm invasion, anthropogenic drivers like urbanization and ongoing global warming will continue to expand palm ranges and promote non‐native palms as generators of novel ecosystems.